Pengaruh Model Pembelajaran Kooperatif Tipe Make a Match oleh Guru PAK terhadap Keaktifan Belajar Siswa Kelas VIII SMP Negeri 2 Sipoholon Tahun Pembelajaran 2023/2024 (Jurnal Pendidikan Agama dan Teologi, 2024)
The learning model really determines the success of learning, including students' active learning. This Research Aims To Determine The Effect of The Make A Match Type Cooperative Learning Model by PAK Teachers On The Active Learning of class VIII students at SMP Negeri 2 Sipoholon for the 2023/2024 Academic Year. The method used in this research is a quantitative method, a type of pre-experimental approach with the design form "One Group Pretest-Posttest Design". The population was all 120 students of class VIII of SMP Negeri 2 Sipoholon who were Christians and a sample of 30 people was determined, namely class VIII 3 using purposive sampling technique. Data analysis used the paired sample t-test. After conducting a pretest and posttest on the sample, the results of data analysis showed that the tcount > ttable value was 24.814 > 1.699. So H1 is accepted and H0 is rejected. Based on the results of this research, it is known that by using the make a match type cooperative learning model, student learning activity can increase, this can be seen from the average score of 72.567 to 88.833 with a difference of 16.267. Thus, it can be concluded that the research hypothesis is accepted, namely that there is a positive and significant influence of the make a match type cooperative learning model by PAK teachers on the learning activity of class VIII students at SMP Negeri 2 Sipoholon for the 2023/2024 academic year.